G616 "We want to influence": An evaluation of the national health service England youth forum. (27th April 2016) - Whiting, LS; Roberts, SA
Abstract : Aims: Presentation aim: To provide an overview of a qualitative evaluation study of the National Health Service England Youth Forum [NHSEYF] (https://www.england.nhs.uk/ourwork/patients/public-voice/yth-for/ ), commissioned by NHS England[NHSE] and undertaken by the University of Hertfordshire between October 2014 and March 2015. Research aim: To enhance insight and understanding of the NHSEYF, its value, role and impact. Methods: A goal-free evaluation research approach, purposive sampling and qualitative data collection methods were utilised to facilitate the undertaking of two focus groups – one with five members of the NHSEYF (15–21years) and one with five members of the adult reference group that supported the NHSEYF. Semi-structured interviews were also conducted with four employees who had played a pivotal role in the establishment of the NHSEYF. A thematic approach (Braun and Clarke, 2006) was drawn on facilitate data analysis. Results: The NHSEYF was formed, primarily, in response to key government documents. The young people, who were members of the NHSEYF, displayed a strong commitment to its work – this necessitated substantive amounts of personal time; they participated in a range of activities, including attendance at the NHSEYF residential weekends, prominent national and local events, engagement with social media. The research revealed evidence of the influence that the NHSEYF work was having at all levels. The NHSEYF young people were able to benefit personally in terms of "confidence building" ; "skills development ; "empowerment". A collaborative approach was fundamental – this enhanced dissemination of the NHSEYF work and engagement with the wider community. The publicity that the NHSEYF received meant that members were in demand; this had the potential to impact on other aspects of their lives. Challenges lie ahead: Expanding the NHSEYF work and building regional teams. The need to further evidence the NHSEYF work. Conclusion: The NHSEYF is still in its infancy, but the research revealed tangible examples of its impact – for instance, the members have designed posters reflecting Youth Rights in Health Care (NHSE, 2015). The research confirmed that young people are very capable of participating in decision-making and that they are ideally placed to inform future health service provision. References: Braun, V. and Clarke, V. Using thematic analysis in psychology. Qualitative Research in Psychology . 2006;3 (2):77–101 NHSE (2015) https://www.england.nhs.uk/wp-content/uploads/2015/08/youth-rights-in-hlthcr-er.pdf